1087 Establishing Guidelines for VTE Prophylaxis for Acute ENT Admissions. (12th October 2021) - Wallace, J; Hepburn, K; O'Hanlon, J; Davis, S
Abstract: Aim: VTE prophylaxis is a vital aspect of patient safety. The decision whether to offer pharmacological thromboprophylaxis is a balance of risk versus benefit. There is a low incidence of VTE in ENT patients, admissions are often short and active bleeding on admission is not uncommon (epistaxis patients, already on anticoagulation are particularly difficult to manage}. There are no clear, specialty specific guidelines to assist in these frequently encountered endeavours. Method: The number of emergency ENT admissions who had a documented VTE during admission or in the 28 days following was used to calculate the incidence of VTE in acute admissions. An audit of VTE prophylaxis and documentation was also conducted using 20 admissions over 24 hours. Results: Incidence was 0.12%. 75% had a documented VTE risk assessment. Only 50% patients were prescribed chemical and mechanical thromboprophylaxis. 0% had appropriately documented that the patient did not require thromboprophylaxis on the drug chart (as per trust guidelines). Conclusions: The results showed that both documentation and prescribing related to VTE prevention were poor. By highlighting the low incidence amongst this patient group, we were able to establish clearer guidance for VTE prophylaxis in acute ENT admissions and a protocol to standardise the management of anticoagulation in actively bleeding epistaxis patients.